Interrelation study between drugs and oral lesion development in patients with special needs - Monteiro, Briana Góes; Azoubel, Maria Cecília Fonsêca; Dantas, Juliana Borges de Lima; Medrado, Alena Ribeiro Alves Peixoto (Journal of Oral Diagnosis, 2019)
Introduction: Special dentistry is an area that of dentistry that concerns itself with tre- ating patients with special needs. To greater knowledge of the specific special needs by the dentist, there is an urgent need to emphasize the importance of proper odontologic treatment, whether in office or in a hospital environment to this population Objectives: The aim of this study was to correlate the use of drugs in patients with special needs with the development of oral lesions and to better characterize this population. Materials and Methods: This was a quantitative and qualitative cross-sectional study which included special needs patients from the Brazil’s Universal Health-Care System. Analysis of medical records and intraoral physical examination was performed for 88 patients and descriptive data was extracted. Results: The patient population was predominantly female (54.5%) and older than 18 years of age (62.5%). A higher frequency of neurological and psychomotor disorders (54.5%), hypertension (29.5%) and diabetes mellitus (15.9%) was found. A total of 21.6% patients reported a”dry mouth.” sensation. The drugs most frequently used were anticonvulsants (46.5%), anxiolytics (35.2%) and anti-hypertensives (34%). The highest percentage of lesions corresponded to gingival enlargement (19.3%), followed by gingivitis (10.2%) and candidiasis (7.9%). Conclusion: It is expected that results derived from this research can contribute to a better understanding of the interrelationship between the use of pharmaceutical agents and the appearance of lesions in the oral mucosa, as well as to indirectly improve oral health of certain patient populations.